2019
DOI: 10.21157/j.med.vet..v13i2.13819
|View full text |Cite
|
Sign up to set email alerts
|

21. α-Amylase and α-Glucosidase Inhibitors from Plant Extracts

Abstract: About 80% of diabetic people have come from developing countries. Indonesia is seventh of diabetics. Diabetes is a disease as a result of metabolic disorder that caused by lack of insulin secretion and/or insulin do not work properly, so that the sugar highly accumulated in blood (characterized by hyperglycemia). Normally, range of blood sugar is 70 - 110 mg / dL before meals and less than 140 mg / dL after meals. One therapeutic approach to control blood sugar level is to inhibit the activity of starch hydrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…The sample material used in this study has the ability to inhibit the activity of α-amylase enzymes. This is thought to be related to the secondary metabolic content in black turmeric, kencur, black cumin, forest bee honey and stevia leaves that are in line with research from M. Daud AK et al (2019) which states that active compounds contained in plant extracts have inhibitory properties good on the activity of the α-amylase enzymes and α-glucosidases such as tannins, flavonoids, polysaccharides, tercent and saponins so that plants that contain active substances are often used as herbal medicines in overcoming high blood sugar levels or preventing diabetes mellitus [21]. This study is in line with research conducted by [22] also said that the α-amylase inhibition mechanism of active biochemical compounds contained in the drug ingredients such as flavonoids, tannins, saponins and terpenes cannot be explained scientifically, But in several studies that have been carried out explains that these compounds are related to the bonds formed between αamylase and the active biochemistry [22].…”
Section: Fig 2 Comparison Of Ic50 Formulation Values 1 Andsupporting
confidence: 69%
“…The sample material used in this study has the ability to inhibit the activity of α-amylase enzymes. This is thought to be related to the secondary metabolic content in black turmeric, kencur, black cumin, forest bee honey and stevia leaves that are in line with research from M. Daud AK et al (2019) which states that active compounds contained in plant extracts have inhibitory properties good on the activity of the α-amylase enzymes and α-glucosidases such as tannins, flavonoids, polysaccharides, tercent and saponins so that plants that contain active substances are often used as herbal medicines in overcoming high blood sugar levels or preventing diabetes mellitus [21]. This study is in line with research conducted by [22] also said that the α-amylase inhibition mechanism of active biochemical compounds contained in the drug ingredients such as flavonoids, tannins, saponins and terpenes cannot be explained scientifically, But in several studies that have been carried out explains that these compounds are related to the bonds formed between αamylase and the active biochemistry [22].…”
Section: Fig 2 Comparison Of Ic50 Formulation Values 1 Andsupporting
confidence: 69%
“…Furthermore, Ningrum, Purwanti, & Sukarsono (2016) research showed that the alkaloids found in the karamunting plant were Maritidine, Homolycorine, Ismine, Tazettine, and Lycorine (Ningrum et al, 2016). α-Glucosidase inhibitor is a type of drug for type 2 diabetes that works to block starch metabolism by inhibiting enzymes in the intestine to break down carbohydrates to slow down glucose absorption (Ak, Juliani, Sugito, & Abrar, 2019;Laily & Khoiri, 2016;Ouassou et al, 2018;Yin, Zhang, Feng, Zhang, & Kang, 2014).…”
Section: Introductionmentioning
confidence: 99%